Comparison between the HLA-B∗58 : 01 Allele and Single-Nucleotide Polymorphisms in Chromosome 6 for Prediction of Allopurinol-Induced Severe Cutaneous Adverse Reactions - Niwat Saksit; Nontaya Nakkam; Parinya Konyoung; Usanee Khunarkornsiri; Wongwiwat Tassaneeyakul; Pansu Chumworathayi; Sirimas Kanjanawart; Chonlaphat Sukasem; Alisara Sangviroon; Oranuch Pattanacheewapull; Wichittra Tassaneeyakul (Journal of Immunology Research)
Severe cutaneous adverse drug reactions (SCARs) are life-threatening reactions. The strong association between the HLA-B∗58 : 01 allele and allopurinol-induced SCARs is well recognized. Screening for HLA-B∗58 : 01 allele before prescribing allopurinol in some populations has been recommended. Several single-nucleotide polymorphisms (SNPs) in chromosome 6 have been found to be tightly linked with the HLA allele, and these SNPs have been proposed as surrogate markers of the HLA-B∗58 : 01 allele. This study aimed to evaluate the association between three SNPs in chromosome 6 and allopurinol-induced SCARs in a Thai population. The linkage disequilibrium between the HLA-B∗58 : 01 allele and these SNPs was also evaluated. Results showed that three SNPs including rs9263726, rs2734583, and rs3099844 were significantly associated with allopurinol-induced SCARs but with a lower degree of association when compared with the HLA-B∗58 : 01 allele. The sensitivity, specificity, PPV, and NPV of these SNPs were comparable to those of the HLA-B∗58 : 01 allele. Although detection of the SNP is simpler and less expensive compared with that of the HLA-B∗58 : 01 allele, these SNPs were not perfectly linked with the HLA-B∗58 : 01 allele. Screening using these SNPs as surrogate markers of the HLA-B∗58 : 01 allele to avoid SCARs prior to allopurinol administration needs caution because of their imperfect linkage with the HLA-B∗58 : 01 allele.